Microfluidic Platform with an Embedded Pencil Graphite Electrode Biosensor for the Detection of Glucose and Cadmium. Issue 2 (1st January 2019) - Torrinha, Álvaro; Montenegro, Maria C. B. S. M.; Araújo, Alberto N.
Abstract : This work describes the study of a nanostructured pencil graphite electrode (PGE) with immobilized glucose oxidase (GOx) having enough robustness to encompass amperometric detection inside microfluidic manifolds. The procedure starts with activation of multi-walled carbon nanotubes (MWCNT) and sequent mixture with GOx. Further addition of ammonium sulfate promoted the precipitation of the enzyme in the vicinity of the nanotubes afterwards stabilized through cross-linking with adding of glutaraldehyde. The obtained solid was then suspended in a nafion solution and finally deposited over the surface of a PGE previously modified with reduced graphene. The approach enabled high and constant enzyme activity, improved stability of the biofilm coating over PGE surface and its use under flow regimen inside microfluidic platforms. In this last condition, the sensitivity achieved corresponded to 35 μA mM −1 cm −2 in a three order of magnitude analytical range up to 39 mM glucose and with a detection limit of 14.9 μM. The biosensor was also applied for the competitive detection of cadmium through an inhibitory effect on GOx, providing the sensitivity of about 1.0 μA mM −1 .